2020
DOI: 10.1002/jbm.a.37106
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects of Chondrus armatus carrageenans and their low molecular weight degradation products

Abstract: Ability of high molecular weight (HMW) κ‐ and λ‐carrageenans of the red marine algae Chondrus armatus and their low molecular weight degradation products (LMWDPs) (0.7–20 and 10–170 kDa respectively) to influence functional properties (motility and phagocytosis) of murine peritoneal macrophages was assessed in this study as an in vitro and a weeklong feeding experiment. We demonstrated that, with an exception of one, all carrageenan samples at 100 μg/ml increased cellular motility and dose‐dependently decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…These results agree with some previous studies in which immune suppressant effects of CGN in vivo have been observed. 21 Considering that degraded CGN is used as an experimental inflammation model, similar to the dextran sulfate sodium (DSS) colitis model, 45 the potential hydrolysis of CGN by the gut microbiota could have favored the damage caused by low- M w CGN products to the intestinal barrier permeability. 35 The sulfate groups from the polygalactan could facilitate disturbing the intestinal mucus layer by making it more permeable to gut microbiota that reach the epithelial cells and trigger an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with some previous studies in which immune suppressant effects of CGN in vivo have been observed. 21 Considering that degraded CGN is used as an experimental inflammation model, similar to the dextran sulfate sodium (DSS) colitis model, 45 the potential hydrolysis of CGN by the gut microbiota could have favored the damage caused by low- M w CGN products to the intestinal barrier permeability. 35 The sulfate groups from the polygalactan could facilitate disturbing the intestinal mucus layer by making it more permeable to gut microbiota that reach the epithelial cells and trigger an inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] There are scarce studies on the effects of CGN on the function and oxidative stress of leukocytes, and these have shown contradictory results. [19][20][21] Moreover, the effects of CGN ingestion on several relevant immune functions and redox parameters of peritoneal leukocytes from mice are unknown. Therefore, the objective of this study was to test the in vivo effects of feeding CGN, at exposure values assessed for children, 4 on the gut microbiota and the intestinal homeostasis of young male and female mice.…”
Section: Introductionmentioning
confidence: 99%
“…The application of λand κ-carrageenan derived from C. armatus has been found to enhance the motility of macrophages while simultaneously reducing their phagocytic activity (Table 1). This characteristic renders these carrageenan compounds suitable for application as immuno-modulatory materials [108].…”
Section: Anti-tumor and Immunomodulation Activitymentioning
confidence: 99%
“…Выделение каррагинанов проводили методом горячей водной экстракции с последующим высаждением 95 % спиртом этиловым. Фракционирование полученного полисахарида осуществляли с помощью 4 % раствора KCl, по описанной ранее методике [8]. Уменьшение молекулярно-массового распределения отдельных фракций проводили методами ультразвуковой (УЗ) деполимеризации (λ-и κ-каррагинан), кислотного гидролиза (κ-каррагинан) и автогидролиза (λ-каррагинан).…”
Section: материалы и методыunclassified